The effectiveness of segregation bins in sample areas belonging to the institutional, commercial and residential sectors in Iloilo City - Convocar, Red Gabriel; Duavis, Mel Simon; Juaneza, Jeannette; Libatique, Clarisse; Nierves, Patrick John.; Prado, Maria Luisa; Saturnino, Ellen Rose.; Sotes, maria Kristina Yve. (2010.)
The disposal of garbage in society is a problem that continues to grow with the development and industrialization and the growth of population. solid waste management policies are implemented to ensure an effective waste management program in the Iloilo City. This study aims to capture the effectiveness of segregation bins in influencing the public's manner in disposing waste in certain settings in Iloilo City. It aims to distinguish the effectiveness of various segregation bins and create relevant quantitative data regarding the study. Furthermore, the paper seeks to determine the waste disposal behavior in schools, malls, and barangays particularly in UPV-CM, The Atrium mall, and Brgy. San Felix, Ybiernas. This research work then will provide possible solutions to answer the growing problem of poor waste disposal. a multi-stage, random-sampling, and survey was done to respondents of uPV and Brgy. San Felix Ybiernas, to determine their opinion on solid waste management, the problem faced, and their preferences on waste segregation. The accuracy on waste thrown on segregated bins is measured in UPV and the Atrium mall. The data gathered reveals that that segregated bins are effective in UPV-CM except for the "Mapuslan" bin. The segregation bins in the Atrium mall are not effective. Although the segregation bins and management in Brgy. San Felix are effective, they still encountered problems in its consistency i the collection schedule. Results show that there is no significant difference on the awareness, obedience of waste management policies, and preferred mode of segregation when variables are grouped according to age and sex.
Research Project (Mgt 199). -- [Iloilo City : University of the Philippines in the Visayas - College of Management], October 2010.